Lanskap Elemen Retorika Komunikasi Pemasaran dalam Bentuk Jargon Iklan sebagai Pengubah Sikap Pemirsa Televisi - Pramudibyanto, Hascaryo (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2024)
Jargon or slogans are essential elements in television advertisements, designed to be memorable and to influence the audience's perception and attitude towards the product. This study aims to analyze the impact of using advertising jargon on television on audience attitude changes within the context of information science. Data was collected through a survey using a questionnaire involving 83 respondents from various age groups and occupations. The study explores the audience’s understanding of advertising jargon, the positioning of the jargon within the ads, and the emotional and cognitive appeal it generates. The findings show that 92.77% of respondents understand the jargon used in advertisements, and the majority find advertising jargon highly appealing (83.13%). Most respondents (72.29%) identified that jargon is typically placed in the middle of the advertisement, where audience attention is at its peak. Additionally, 73.49% of respondents felt compelled to purchase the product due to the jargon used. This indicates that jargon plays a significant role in creating emotional appeal and enhancing the audience's memory of the advertised product. Overall, this study reinforces the importance of using advertising jargon in television as an effective tool for shaping perceptions and influencing consumer purchase decisions.